Evaluation of antioxidant properties, elemental and phenolic contents composition of wild nettle (Urtica dioica L.) from Tunceli in Turkey - Yildirim, N. C.; Turkoglu, S.; Ince, O. K.; Ince, M. (Cellular and Molecular Biology, 2013)
Wild nettle (Urtica dioica L.) types were sampled from different geographical regions in Tunceli (Turkey) to determine their mineral, vitamin, phenolic contents and their antioxidant properties. The total phenol varied from 37.419±0.380 to 19.182±1.00 mg of GAEs g-1 of dry nettle. The highest radical scavenging effect was observed in Mazgirt parting of the ways 7.5 km with 33.70±0.849 mg mL-1. The highest reducing power was observed in the nettles from Mazgirt parting of the ways 7.5 km. Among the various macronutrients estimated in the plant samples, potassium was present in the highest quantity followed by calcium and phosphate. Kaempferol and resveratrol were not determined in some nettle samples but rutin levels were determined in all samples. Vitamin A concentrations were ranged between 13.64±1.90 and 5.74±1.00 (mg kg-1 dry weight). These results show that Urtica dioica L. collected from Tunceli in Turkey could be considered as a natural alternative source for food, pharmacology and medicine sectors.